Orbital relapse in children treated for Pre-B ALL, a retrospective case series - Komal Seher; Saadiya Javed Khan (Journal of the Pakistan Medical Association, 2020)
Abstract About 85-90% of children with B-cell leukaemia are cured. If relapse occurs it is usually in the bone marrow (BM), followed by extramedullary sites. Ocular lesions occur secondary to the accumulation of circulating blasts in the uvea, optic disc, intra-ocular tissue as well as fluid. Here we report four patients with ocular complaints that led to the diagnosis of relapse. Among 475 children with leukaemia treated from January 2013 to December 2018, 50 (10.5%) patients relapsed. Four (8%) out of these 50 presented with orbital symptoms. Central Nervous System (CNS) evaluation by cerebrospinal fluid (CSF) was negative at relapse. Relapse was treated with chemotherapy R3 protocol. Three (75%) patients are alive, while the fourth patient had a second BM relapse and died. Ophthalmic signs and symptoms in patients with treated leukaemia warrant a thorough evaluation. Continuous...